A Control Chart for Exponentially Distributed Characteristics Using Modified Multiple Dependent State Sampling. (28th December 2020) - Albazli, Ahmad O.; Aslam, Muhammad; Dobbah, Saeed A.
Abstract : In this paper, a t -control chart based on modified multiple dependent state sampling is proposed for monitoring processes that assume time between events following exponential distribution. The chart has double control limits and employs information from a previous sample and the current sample. The control chart coefficient "constants" are estimated by considering different values of the in-control average run lengths. The detection ability of the proposed control chart is found to be better than that of control charts based on multiple dependent state sampling in terms of average run lengths and the standard deviation of run lengths and better than generalized multiple dependent state sampling in terms of average run lengths. Case studies with real data are included as illustrative examples for the implementation of the proposed chart.